Perancangan Ulang Tata Letak Fasilitas Produksi dengan Metode Systematic Layout Planning dan BLOCPLAN untuk Meminimasi Biaya Material Handling pada UD. Sofi Garmen - Ulfiyatul Kholifah; Suhartini (Journal of Research and Technology, 2021)
The competitions among industries will get increasing and grow rapidly along with the advan/cement of technology. The layout of company facilities must be considered well as it holds a vital role in determining the quality of production process. Sofi Garmen Firm has encountered a problem of far distance in material handling among departments that finally triggered disturbance of production activity and huge cost of material handling. Therefore, a design for relayouting production facilities became the research object. It aimed at designing the layout proposal through Systematic Layout Planning and Blocplan methods. To calculate the distance, the researcher employed Rectilinear and Euclidean. The result of both distance calculations in Systematic Layout Planning obtained 29,678.5 meters and 23,375 meters respectively, whereas the cost of material handling gained averagely IDR 1,129,356.5. Meanwhile, the results of distance calculations of Rectilinear and Euclidean in Blocplan earned 30,920 meters and 26,942.5 meters consecutively and the cost of material handling produced averagely IDR 1,237,564.5. Accordingly, the calculation results indicated that the recommendation yielded by Systematic Layout Planning became the most optimum alternative of layout.